2011
DOI: 10.3928/1081597x-20110725-01
|View full text |Cite
|
Sign up to set email alerts
|

Glistenings on Intraocular Lenses in Healthy Eyes: Effects and Associations

Abstract: In healthy eyes, glistening grade was not associated with contrast sensitivity, CDVA, intraocular light scatter, or any lens or demographic characteristics that were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 16 publications
3
42
0
1
Order By: Relevance
“…In total, 6 studies examined the effect of glistenings on CS. Four of these studies reported that glistenings had a significant negative effect on the high spatial frequency CS [1][2][3][4] and two studies were non-conclusive [5,6]. While some studies do show a decrease in VA with increased severity of glistenings [6,7] the general consensus in the literature tends to be that visual acuity is unaffected by glistenings [1][2][3]5,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…In total, 6 studies examined the effect of glistenings on CS. Four of these studies reported that glistenings had a significant negative effect on the high spatial frequency CS [1][2][3][4] and two studies were non-conclusive [5,6]. While some studies do show a decrease in VA with increased severity of glistenings [6,7] the general consensus in the literature tends to be that visual acuity is unaffected by glistenings [1][2][3]5,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 90%
“…The glistenings formation, as well as the severity of glistenings, has been correlated with longer follow-up times [3,7,10,[24][25][26]. Very few studies that evaluate the progression beyond one year find glistening formation to be stable [5,6]. Temperature fluctuations in the eye are mentioned as one of the factors for this progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Similarly, five studies have shown decreased contrast sensitivity for the higher spatial frequencies when glistenings are present in the body of the IOL optic, [17][18][19][20][21] and two studies were nonconclusive. 22,23 Despite these studies, general understanding of the implication of these relatively low levels of retinal iovs.arvojournals.org j ISSN: 1552-5783 stray light on visual function is limited and uncertain even in cases when retinal stray light is measured and quantified. 4,[23][24][25] Therefore, in this study, an improved contrast sensitivity test, with and without the presence of a glare source, and a luminance detection threshold test are used to create quantifiable visual performance measures of the impact of retinal stray light.…”
mentioning
confidence: 99%
“…However, the 'defects' caused by glistenings are deemed too small to influence straylight. 25 In this study, none of the IOLs showed significant glistenings in the 3 months of follow-up. As a result, glistenings do not seem to play a role in the higher straylight of the hydrophobic lens group.…”
Section: Straylight Measurements/lapid-gortzak Et Almentioning
confidence: 89%